PENGARUH FIKSATOR PADA EKSTRAK AKAR MENGKUDU TERHADAP PEWARNAAN JUMPUTAN - Enggar Kartikasari (KELUARGA: Jurnal Ilmiah Pendidikan Kesejahteraan Keluarga, 2015)
This research generally try to determine  the effect of natural fixator from noni root   extract to dye coloring technique. The         hypothesis of this research is : There are     positive effect and significant between noni root extract in terms of color fading resistance. This research was conducted on laboratory. The population of this research was : dyeing, noni root extract, lime fixator and quicklime. Data collecting through the experiment.      Data analysis using the grey scale based        on SNI. The result shows that there are positive effect and significant because the fixator has a good resistance against the color fading on noni root extract through the ironing process. Visually, dyeing result without fixation produce a dull brown color, lime fixator tend to produce a yellowish brown and quicklime fixator tend to produce a reddish brown color.